Filosofia na escola: a constituição da disciplina a partir das práticas docentes - Marçal, Katiuska Izaguirry (2012)
The question about the possibility of the spread of philosophical activity in school - a typical institution of our society that bears the responsibility to convey the ways of thought that exist in our culture - constitutes an important aspect in the recent history of (re) inclusion of the discipline of philosophy in high school in Brazil. It is under such a paradigm that has emerged this research proposal, belonging to the Research Line 2: School Practice and Public Policy, of the Postgraduate Program in Education of the Federal University of Santa Maria. His goal was to investigate the discourses that permeate the school, the philosophy class and subjectteachers of philosophy, and that, somehow, produce an apparent separation between the teaching of philosophy and philosophizing. The materiality of this research are documents of public policies on education and the discipline of philosophy, the documents of the schools and / or institutions of higher education, philosophical and academic texts (who hold forth on education, teaching philosophy, activity of philosophizing), but fundamentally, the words of teachers of philosophy. It is assumed therefore that the subject represented by the teacher is likely of the intersection of various discourses constitute the knowledge on philosophy and education, contemporaneously. The reading of both documents as the speeches - from semistructured interviews - was in the exercise of an archaeogenealogic discourse analysis, as the postulates developed by Michel Foucault. In this sense, the project introduces and develops concepts such as speech, utterance, archeology, genealogy, and subject of discourse. Therefore, as a result of this investigation, we highlight certain conceptions of philosophy, philosophizing and teaching of philosophy crossed by referring, as: teaching / research, history of philosophy, classic text, critique, dialogue, think / thought,practice, and so. The pedagogical practices indicated by these units of discourse present tensions. These concepts are created by philosophy itself, and therefore denote paradoxes related to the philosophy and teaching of philosophy. They refer to the Kantian sentence Philosophy is not taught. It is taught to philosophize. Finally, the study turns to an analysis of strategies of power and governmentality made in school in order to understand the relationship between teacher discourse and its institutional and political constraints. There is consonance between teaching practices and certain disciplinary and control concepts.